2021
DOI: 10.5937/mkng2102103b
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive biases in marketing communication: Influence of anchoring and message framing on consumers' perception and willingness to purchase

Abstract: While in the theory of rational decision making, it is considered that people's choices remain consistent and predictable even in cases when same information is presented in different ways, in real situations consumers' decisions are affected by their personal characteristics, habits, norms and past experience, as well as limitations of human cognitive mechanisms. In general, heuristics can be perceived as fast cognitive processes in decision making which can sometimes lead to the occurrence of biases which sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Based on past research, it is not clear if preferential judgments such as compensation demands are robust to the influence from anchoring, or whether they too are susceptible to anchoring effects just like judgments of objective facts (Andersson et al ., 2021; Bunčić et al ., 2021; Yoon et al ., 2019). The susceptibility to extraneous information on these compensation demand judgments, as found in the current paper, suggests that compensation demands are not fixed.…”
Section: Discussionmentioning
confidence: 99%
“…Based on past research, it is not clear if preferential judgments such as compensation demands are robust to the influence from anchoring, or whether they too are susceptible to anchoring effects just like judgments of objective facts (Andersson et al ., 2021; Bunčić et al ., 2021; Yoon et al ., 2019). The susceptibility to extraneous information on these compensation demand judgments, as found in the current paper, suggests that compensation demands are not fixed.…”
Section: Discussionmentioning
confidence: 99%
“…This application also comes from an experiment. In studying marketing communication, Bunčić et al found that by exploiting the anchoring effect, businesses could sell more goods and make more money [8]. The purpose of this experiment is to test the use of cognitive bias in advertisements.…”
Section: Application 3 -Marketingmentioning
confidence: 99%